PENGGUNAAN INTERNET SEBAGAI MEDIA PEMBELAJARAN PADA MAHASISWA IAIN PALU - Said, Hamka (State Institute of Islamic Studies (IAIN) Palu, 2015)
This article is the result of research on the use of the Internet as a medium of learning in students of IAIN Palu. This study used descriptive qualitative approach. The results show: first, use of the Internet as a medium of learning in Palu IAIN can be mapped into three categories, namely: the use of web searching facility, the use of e-mail facilities, and the use of e-learning facilities. Secondly, in terms of infrastructure, hardware to support internet-based learning is sufficient, but the amount of bandwidth is still very far from the standard requirements. Meanwhile, in terms of human resources, still need to increase their knowledge and skills in the field of IT for teachers and students to be able to implement an optimal internet-based learning. Third, Palu IAIN students responded very positively to the use of the Internet as a medium of learning.